A NEW GUINEA CINNAMON USED AS A CONTRACEPTIVE - kostermans, a. j. g. h. (Research Center for Biology, 1969)
In 1966 an expedition worked in W. Irian to find the sources of vegetal medicaments for practising contraception. Dr. W. Soegeng Reksodihardjo and myself were assigned to locate the plants and to bring the material together. The field testing (vaginal smears of injected white mice) was carried out by Dr. R. C. Barnett, whereas the Office of General Hartono of the Indonesian Army provided transportation.